L’hypothèse de la traduction artiviste : mise en chantier indisciplinaire - Myriam Suchet; Sarah Mekdjian (Itinéraires)
This article deals with urban practices which combine art and political action. Can setting up an informal vegetable garden in a street, turning maps or road signs around, etc. be analysed as many forms of translation? Our hypothesis is to think of artivist works and practices as acts of translation by considering that these practices operate displacements within city spaces (plan of the analysed object) and by operating ourselves translations (meta-plan of analysis). In doing so, we become heterolingualist (Myriam Suchet) and geographist (Sarah Mekdjian) in order to experience what changes in our way of thinking when we tie together research, action and creation—what we call an indisciplinary perspective. We start by establishing an ad hoc typology of various artivist installations, principally based in Montreal in order to redefine translation in terms of “battement” and “interstice” before developing it into a hypothesis for the analysis of creative cartographic practices carried out in Grenoble in 2013.